G - C3N4 (2D)/CdS (1D)/rGO (2D) dual-interface nano-composite for excellent and stable visible light photocatalytic hydrogen generation - Tonda, Surendar (International Journal of Hydrogen Energy, 2017)
A 2D/1D/2D dual-interface nano-composite configuration in the form of CdS nanorods sandwiched between g-C3N4 and rGO sheets with intimate interfacial contact is synthesized by a facile wet-chemical method and is shown to exhibit excellent photocatalytic H2 generation under visible-light irradiation. In particular, the optimal g-C3N4/CdS/rGO dual-interface nano-composite shows H2 production rate of ∼4800 μmol h-1 g-1, which is almost 44, 11 and 2.5 times higher than that shown by pure g-C3N4 nanosheets, and the g-C3N4/rGO and g-C3N4/CdS single interface heterostructures, respectively. It is shown that the synergic effects involving the band structure match and close interfacial contact, which can accelerate the separation and transfer of photoinduced charge carriers, and the enhanced visible-light absorption together contribute to the impressive photocatalytic performance and photostability of the g-C3N4/CdS/rGO ternary nano-composite system. Specific advantages of a dual-interface triple-composite system over a single interface case(s) are also brought out.
Keywords: charge transfer; Dual Interface; G - CN; H Generation; Hetero Structure; Nano - Composite